2004
DOI: 10.1002/poc.808
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and binding properties of different multiple‐state glycine–Fe+/Fe2+ complexes

Abstract: Several biologically relevant glycine-Fe þ /Fe 2þ complexes with three different multiplicities were studied for the first time by using the hybrid three-parameter B3LYP density functional method with different basis sets. Single-point calculations were also carried out at the BHLYP level with a larger basis set to refine and calibrate these energy values. The results show that the most stable glycine-Fe þ isomer is the C 1 -symmetric sextet NO-16, in which Fe þ is interacted with both the amino nitrogen and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
1
27
1
Order By: Relevance
“…The B3LYP method provides similar structural parameters compared with the MP2 method, and the vibrational frequencies and intensities are in excellent agreement with the experimental data while requiring far less disk space 1016. In addition, previous studies have shown that B3LYP is very well‐suited for ion–ligand complexes 15. 17…”
Section: Methodssupporting
confidence: 60%
“…The B3LYP method provides similar structural parameters compared with the MP2 method, and the vibrational frequencies and intensities are in excellent agreement with the experimental data while requiring far less disk space 1016. In addition, previous studies have shown that B3LYP is very well‐suited for ion–ligand complexes 15. 17…”
Section: Methodssupporting
confidence: 60%
“…4,24,25,29 Because of the presence of a third negatively charged center in the side chain of Glu, the interaction between the metal ion and the side-chain carbonyl group can further stabilize the complexes, leading to the preferred tridentate NOOs coordination for Glu−TMC + .…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] In addition, previous studies have shown that B3LYP is very well-suited for ion-ligand complexes. [15,17] Full geometry optimizations without any symmetry constraints, vibrational frequency analyses, and the corresponding zero-point vibrational energy (ZPVE) analyses were performed at the B3LYP/6-31 + G* level of theory. Furthermore, the relevant energies and other parameters of the optimized isomers and the transition-state structures were determined at the B3LYP/6-311 + G* level with the geometries taken from the B3LYP/6-31 + G* level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we computed the electrostatic interaction by a very simple pointcharge model, that is, the energy lowering of the deformed nifedipine in the presence of a positive double charge (+ 2) at the same metal-nifedipine distance. [14,15] As the electrostatic relaxation of nifedipine was allowed, the actual lowering also includes the polarization term. Table 1 shows the deformation and the electrostatic contribution to the binding energy of calcium-ion binding to the isolated nifedipine molecule, and includes the relative energies before and after ZPVE corrections of the nifedipine-Ca 2 + complexes.…”
Section: Relative Energies and Main Contributions To The Binding Enermentioning
confidence: 99%